Determinants of place of death among individuals with cardiovascular disease: A Saudi sub-national register study - Ahmed Alshehri; Faleh Alyazidi; Mária Bartušová; Mayssa Rekhis; Leo Stockfelt; Laith Hussain-Alkhateeb (PLoS ONE, 2025)
Understanding the place of cardiovascular disease (CVD) deaths is essential for identifying vulnerable populations and guiding health system interventions. This study investigated the demographic and clinical determinants of the place of death among individuals with CVD in Makkah City, Saudi Arabia. We analyzed 9,652 CVD death records from two major hospitals (2018−2023) for decedents aged ≥18 years, including the place and year of death, sex, age, citizenship, and causes of death (ICD-10). Chi-square tests assessed associations and multivariable logistic regression identified independent predictors of out-of-hospital deaths. Out-of-hospital deaths accounted for 90.0% of all CVD deaths. Within each age group, the proportion of deaths that occurred out-of-hospital was highest among the youngest (18–45 years, 92.8%) and oldest (76 + years, 90.1%) age groups, with lower levels among middle-aged adults (46–60 years, 88.2%; 61–75 years, 86.6%). By citizenship, 92.6% of non-Saudis (n = 4,273), 90.8% of pilgrims (n = 2,248), and 84.0% of Saudis (n = 2,150) died outside hospital settings. There were significant associations between place of death and age, citizenship, ethnicity, and cause of death (all p < 0.001). Out-of-hospital deaths declined from 93.6% in 2018 to 77.2% in 2023, but sudden cardiac death (SCD) had the highest proportion (93.6%). Adjusted analyses showed higher odds of out-of-hospital death for non-Saudis (aOR = 2.05, 95% CI: 1.47–2.85) and pilgrims (aOR = 1.91, 95% CI: 1.38–2.66) compared with Saudis. SCD was strongly associated with out-of-hospital death compared with ischemic heart disease (aOR = 46.74, 95% CI: 37.35–58.48). Despite recent declines, most CVD deaths occurred outside hospitals, particularly among non-Saudis and in the youngest and oldest age groups. The predominance of SCD especially in out-of-hospital cases, may reflect diagnostic limitations and possible misclassification when clinical assessment is unavailable. Strengthening medical certification processes, improving access to timely emergency care, and exploring the role of factors such as health insurance, indirect costs, and health literacy in future research are priorities for reducing preventable CVD mortality.